The crisis of democratic theory : scientific naturalism & the problem of value - Purcell, Edward A. ([Lexington] : University Press of Kentucky, 1973)
Widely acclaimed for its originality and penetration, this award-winning study of American thought in the twentieth century examines the ways in which the spread of pragmatism and scientific naturalism affected developments in philosophy, social science, and law, and traces the effects of these developments on traditional assumptions of democratic theory.
The problems of democratic theory -- Scientific naturalism in American thought -- The undermining of democratic theory -- Naturalism & objectivism in the social sciences -- Methodology & morals -- Non- Euclideanism : logic & metaphor -- The rise of legal realism -- The new study of politics -- The crisis of democratic theory -- America & the rise of European dictatorships -- Counterattack -- Crisis in jurisprudence -- Crisis in social science -- Toward a relativist theory of democracy -- Theoretical principles & foreign policy -- The resolution of democratic theory -- Relativist democratic theory & postwar America -- America as a normative concept.
Includes bibliographical references.
Print version record.
JSTOR
Keywords: Social sciences -- United States -- History; Naturalism; Democracy; Naturalisme; naturalism (philosophical movement); SOCIAL SCIENCE -- Essays; SOCIAL SCIENCE -- Reference; SOCIAL SCIENCE -- General; Democracy; Naturalism; Social sciences; United States; Demokratie; Krise; Theorie; Democratie; Politieke wetenschappen; Electronic books; History